2014
DOI: 10.7196/samj.8419
|View full text |Cite
|
Sign up to set email alerts
|

The Vaccine and Cervical Cancer Screen (VACCS) project: Acceptance of human papillomavirus vaccination in a school-based programme in two provinces of South Africa

Abstract: Cervical cancer remains an important cause of morbidity and mortality in South Africa (SA). [1] The age-standardised incidence rate of cervical cancer in southern Africa is approximately 27/100 000, [2] and most cases are diagnosed in late stages. Persistent infection with oncogenic human papillomavirus (HPV) is an essential step in the development of invasive cervical cancer. [3] HPV is highly infectious, but does not cause disease in all cases, and most individuals will clear infections. Since HPV is almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 13 publications
0
50
1
3
Order By: Relevance
“…Outcomes of the vaccination programme and the main results of the selfscreening study have been reported elsewhere. [12] …”
Section: Methodsmentioning
confidence: 99%
“…Outcomes of the vaccination programme and the main results of the selfscreening study have been reported elsewhere. [12] …”
Section: Methodsmentioning
confidence: 99%
“…A feasibility trial for the upcoming government-funded program in England had high rates of HPVV initiation after the first year (70.6%), despite challenges with vaccine delivery and multiple missed appointments. 57 Programs in Brazil and South Africa included education campaigns and free vaccination, demonstrating uptake rates of 85% 64 (completion) and 58.6% 56 (at least 1 dose), respectively. Similar implementation challenges faced both programs: parents refusing to participate (up to 41%) 56 or not attending educational classes.…”
Section: Environmental Interventions (N = 31)mentioning
confidence: 99%
“…57 Programs in Brazil and South Africa included education campaigns and free vaccination, demonstrating uptake rates of 85% 64 (completion) and 58.6% 56 (at least 1 dose), respectively. Similar implementation challenges faced both programs: parents refusing to participate (up to 41%) 56 or not attending educational classes. 56 Two school-based VPs in the United States included free HPVV.…”
Section: Environmental Interventions (N = 31)mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, medical aids are encouraging vaccination of boys also! In this issue we publish the first of a series of three papers that trumpet the success of the Vaccine and Cervical Cancer Screen (VACCS) project, [1,2] a school-based HPV vaccination project that gives reality to the announcement in May 2013 by Dr Aaron Motsoaledi, Minister of Health, that '… we shall commence to administer the HPV vaccines as part of our school health programme ... ' against a background of an uncontrolled cervical cancer epidemic resulting from high prevalences of HPV and HIV and a relatively unsuccessful cervical cancer screening programme.…”
Section: Preventing Cervical Cancermentioning
confidence: 99%